2017
DOI: 10.1128/jvi.00320-17
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Protein Heterogeneity within Herpes Simplex Virus 1 Particles

Abstract: Several virulence genes have been identified thus far in the herpes simplex virus 1 genome. It is also generally accepted that protein heterogeneity among virions further impacts viral fitness. However, linking this variability directly with infectivity has been challenging at the individual viral particle level. To address this issue, we resorted to flow cytometry (flow virometry), a powerful approach we recently employed to analyze individual viral particles, to identify which tegument proteins vary and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 56 publications
4
44
0
2
Order By: Relevance
“…The goodness of fit to a normal distribution of VP5 intensities exceeded 0.95 with a CV of 23.75 (S3 Fig). This variance in particle intensity is very similar to analogous types of HSV single particle analysis using either GFP-fusion proteins or antibody to capsid protein [32,33]. With this as a benchmark, we found the distribution genome signal detected by cycloaddition to have only marginally increased variance with a CV of 34.19 and a goodness of fit to normal of 0.94 (S3 Fig).…”
Section: Production and Genome Detection In Hsv Virions Containing Edcsupporting
confidence: 64%
“…The goodness of fit to a normal distribution of VP5 intensities exceeded 0.95 with a CV of 23.75 (S3 Fig). This variance in particle intensity is very similar to analogous types of HSV single particle analysis using either GFP-fusion proteins or antibody to capsid protein [32,33]. With this as a benchmark, we found the distribution genome signal detected by cycloaddition to have only marginally increased variance with a CV of 34.19 and a goodness of fit to normal of 0.94 (S3 Fig).…”
Section: Production and Genome Detection In Hsv Virions Containing Edcsupporting
confidence: 64%
“…The deletion of UL49, coding for VP22 in pseudorabies virus (PRV), has only a minor impact on viral growth (14,15), whereas in HSV-1, the lack of VP22 is rapidly compensated for by mutations in UL41 (16)(17)(18). However, HSV-1 null mutants replicate less efficiently and do not accumulate at the cell surface, and the absence of VP22 affects the virion composition and indirectly modulates viral fitness (19)(20)(21).…”
Section: Importancementioning
confidence: 99%
“…Additional experiments would be required to verify whether some other viral proteins are mislocalized or incorrectly expressed in VZV-ORF9-L231-V5-infected cells and whether the final composition of the released virions is affected. A very elegant flow virometry analysis of the extracellular HSV-1 particles indicates that the particles sorted for their high VP22 content show a modest but reproducible increase in infectivity compared to the particles containing smaller amounts of VP22, although the authors concluded that the VP22 level acts only indirectly on viral fitness (20). Although technically difficult due to the small amount of particles produced, a mass spectrometry analysis of VZV-ORF9-L231A-V5 particles would certainly be informative.…”
Section: Figmentioning
confidence: 99%
“…Despite these exciting initial reports, the analysis of viruses by flow cytometry, which Grivel and colleagues termed "flow virometry" in 2013 (14), has become more mainstream only recently. Flow virometry has now been used to characterize an expanding array of additional viruses, including lambda phage (15), herpes simplex virus 1 (HSV-1) (16,17), mouse hepatitis virus (MHV) (18), human immunodeficiency virus (HIV) (14,(19)(20)(21), Nipah virus (22), Junin virus (23), vaccinia virus (24), dengue virus (20,25), human cytomegalovirus (HCMV) (26), and giant viruses (13). Flow virometry is becoming a powerful tool to characterize viruses.…”
Section: The Birth Of Flow Virometrymentioning
confidence: 99%